2011
DOI: 10.1179/146701011x12950038111819
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in Pendred syndrome

Abstract: Cochlear implantation is the proper method for optimal hearing rehabilitation in patients with Pendred syndrome. Although the precise pathogenetic mechanism and the genetic background of deafness in Pendred syndrome have not been completely understood, the preexisting hearing experience represents a positive factor for satisfying hearing outcome. The inner-ear malformations can cause mild surgical difficulties and extended surgery duration. The cochlear implant surgeon should be aware of these difficulties to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
0
14
0
6
Order By: Relevance
“…Pendred syndrome, the most common syndromic cause of SNHL, is another syndromic condition that is inherited in an autosomal recessive fashion and usually causes congenital SNHL, often at birth, via enlarged vestibular aqueduct, a common inner ear deformity (Smith et al, 2005;Morton and Nance, 2006;Azaiez et al, 2007;Wémeau and Kopp, 2017). Studies of cochlear implantation in children with Pendred syndrome found that they have better speech perception compared to children who are deaf due to enlarged vestibular aqueduct not caused by Pendred syndrome despite the possibility of mild surgical complications due to the inner ear malformations caused by Pendred (Kontorinis et al, 2011;van Nierop et al, 2016;Mikkelsen et al, 2019;Mey et al, 2020). Other studies indicate that early diagnosis of SNHL, followed by cochlear implantation and rehabilitation, is also beneficial in Usher and Waardenburg Syndromes (Young et al, 1995;Loundon et al, 2003;Cullen et al, 2006;Hartel et al, 2017;Alzhrani et al, 2018;Nair et al, 2020).…”
Section: Current Use Of CI In Congenital Hearing Lossmentioning
confidence: 99%
“…Pendred syndrome, the most common syndromic cause of SNHL, is another syndromic condition that is inherited in an autosomal recessive fashion and usually causes congenital SNHL, often at birth, via enlarged vestibular aqueduct, a common inner ear deformity (Smith et al, 2005;Morton and Nance, 2006;Azaiez et al, 2007;Wémeau and Kopp, 2017). Studies of cochlear implantation in children with Pendred syndrome found that they have better speech perception compared to children who are deaf due to enlarged vestibular aqueduct not caused by Pendred syndrome despite the possibility of mild surgical complications due to the inner ear malformations caused by Pendred (Kontorinis et al, 2011;van Nierop et al, 2016;Mikkelsen et al, 2019;Mey et al, 2020). Other studies indicate that early diagnosis of SNHL, followed by cochlear implantation and rehabilitation, is also beneficial in Usher and Waardenburg Syndromes (Young et al, 1995;Loundon et al, 2003;Cullen et al, 2006;Hartel et al, 2017;Alzhrani et al, 2018;Nair et al, 2020).…”
Section: Current Use Of CI In Congenital Hearing Lossmentioning
confidence: 99%
“…Performance was constant over time. Results of seven patients with Pendred syndrome and a CI were analysed by Broomfield (2013) . Speech recognition was measured using Bamford‐Kowal‐Bench sentences.…”
Section: Discussionmentioning
confidence: 99%
“…31 Kontorisnis et al Results of seven patients with Pendred syndrome and a CI were analysed by Broomfield (2013). 32 Speech recognition was measured using Bamford-Kowal-Bench sentences. All of the patients had congenital hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…U pacjentów z zespołem Pendreda należy jak najszybciej rozpocząć rehabilitację dostosowaną do typu i głębokości niedosłuchu pacjenta [1]. Kiedy korzyści ze stosowanych aparatów słuchowych są niewystarczające, tak jak w przypadku innych zespołów genetycznych związanych z występowaniem głębokiego niedosłuchu czuciowo-nerwowego, rozwiązaniem z wyboru jest implantacja ślimakowa [21][22][23][24][25].…”
Section: Diagnoza Zespołu Pendredaunclassified